A porous silicon-carbon negative electrode material, a preparation method thereof, a negative electrode sheet, and a full-tab cylindrical lithium ion battery

CN123017936APending Publication Date: 2026-10-30JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611295098.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有空心多孔硅碳负极技术存在以下关键缺陷:1)壁厚控制粗糙,实际产品批次间性能波动大;2)碳包覆层表征依赖高成本手段;3)未与圆柱电池结构协同设计,即空心多孔硅碳负极的体积膨胀特性与圆柱电池的卷绕结构、全极耳散热之间的耦合关系未进行深度探究;

Benefits of technology

本申请通过建立空心硅颗粒的壳层壁厚与空心率的定量匹配关系,并协同限定多孔硅碳负极材料的振实密度和比表面积,不仅实现了对产品批次一致性的低成本快速检测,而且上述结构参数与全极耳圆柱电池的结构可协同设计,从而有效抑制了循环过程中的硅体积膨胀,使得全极耳圆柱电池可获得高能量密度与长循环寿命的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a porous silicon-carbon negative electrode material, a preparation method thereof, a negative electrode sheet and a full-tab cylindrical lithium ion battery. The porous silicon-carbon negative electrode material comprises hollow silicon particles and a carbon coating layer coated on the outer surface of the hollow silicon particles; the porous silicon-carbon negative electrode material satisfies: 20nm≤δ≤80nm; 30%≤φ≤65%; 0.35g / cm 3 ≤ρ tap ≤0.80g / cm 3 ; 20m 2 / g≤S BET ≤120m 2 / g. The application establishes a quantitative matching relationship between the shell wall thickness of the hollow silicon particles and the hollow ratio, and cooperatively limits the tap density and the specific surface area of the porous silicon-carbon negative electrode material, thereby realizing low-cost and rapid detection of batch consistency of the product, and the above structural parameters and the structure of the full-tab cylindrical battery can be cooperatively designed, so that the volume expansion of silicon in the cycle process is effectively inhibited, and the full-tab cylindrical battery can obtain a synergistic improvement of high energy density and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery materials technology, specifically relating to a porous silicon-carbon anode material and its preparation method, anode sheet, and a cylindrical lithium-ion battery with full tabs. Background Technology

[0002] Silicon (Si) has a theoretical specific capacity of approximately 3579 mAh / g, about 10 times that of graphite (372 mAh / g), making it one of the most competitive anode materials for next-generation lithium-ion batteries. However, Si undergoes a volume expansion of up to ~300% during charge and discharge, leading to particle pulverization, continuous rupture and regeneration of the SEI film, resulting in rapid capacity decay and a decrease in coulombic efficiency.

[0003] Hollow structure design is an effective strategy for buffering silicon volume expansion. The pre-reserved cavities inside hollow silicon particles provide buffer space for the expansion of the silicon shell, while thinning the shell also reduces the absolute expansion, which is beneficial for maintaining SEI stability. However, existing hollow porous silicon-carbon anode technology has the following key drawbacks: 1) Coarse wall thickness control leads to large performance fluctuations between batches of actual products; 2) Characterization of the carbon coating layer relies on high-cost methods; 3) It is not designed in conjunction with the cylindrical battery structure, i.e., the coupling relationship between the volume expansion characteristics of the hollow porous silicon-carbon anode and the winding structure and all-tab heat dissipation of the cylindrical battery has not been deeply explored. Therefore, it is urgent to establish quantitative relationships between the shell wall thickness, hollowness, tap density, and specific surface area of ​​hollow silicon particles, as well as porous silicon-carbon anode materials, to achieve low-cost and detectable analysis and to realize co-design with cylindrical battery structures in order to obtain high-performance cylindrical batteries. This is a technical problem that needs to be solved urgently. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this application aims to provide a porous silicon-carbon anode material, its preparation method, anode sheet, and a fully tabbed cylindrical lithium-ion battery. By establishing a quantitative matching relationship between the shell wall thickness and hollowness of hollow silicon particles, and synergistically defining the tap density and specific surface area of ​​the porous silicon-carbon anode material, this application not only achieves low-cost and rapid testing of batch consistency but also allows for the synergistic design of the aforementioned structural parameters with the structure of the fully tabbed cylindrical battery. This effectively suppresses silicon volume expansion during cycling, enabling the fully tabbed cylindrical battery to achieve a synergistic improvement in both energy density and cycle life.

[0005] To achieve the purpose of this application, the following technical solution is adopted: In a first aspect, this application provides a porous silicon-carbon anode material, the porous silicon-carbon anode material comprising hollow silicon particles and a carbon coating layer covering the outer surface of the hollow silicon particles.

[0006] The porous silicon-carbon anode material satisfies the following conditions: 20nm≤δ≤80nm, where δ is the shell wall thickness of the hollow silicon particle.

[0007] 30%≤φ≤65%, where φ is the hollowness of the hollow silicon particles.

[0008] 0.35g / cm 3 ≤ρ tap ≤0.80g / cm 3 , ρ tap The tap density is the porous silicon-carbon anode material.

[0009] 20m 2 / g≤S BET ≤120m 2 / g, S BET The specific surface area of ​​the porous silicon-carbon anode material is given.

[0010] This application establishes a quantitative matching relationship between the shell wall thickness and the hollowness of hollow silicon particles, and synergistically limits the tap density and specific surface area of ​​porous silicon-carbon anode materials. This not only enables low-cost and rapid detection of batch consistency of products, but also allows the above structural parameters to be synergistically designed with the structure of all-tab cylindrical batteries, thereby effectively suppressing silicon volume expansion during cycling. This enables all-tab cylindrical batteries to achieve a synergistic improvement in high energy density and long cycle life.

[0011] In this application, 20nm≤δ≤80nm, for example, can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, or 80nm, etc.; 30%≤φ≤65%, for example, can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, or 65%, etc.; 0.35g / cm 3 ≤ρ tap ≤0.80g / cm 3 For example, it could be 0.35 g / cm³. 3 0.40 g / cm 3 0.50g / cm 3 0.60g / cm 3 0.70g / cm 3 Or 0.80g / cm 3 Wait, 20m 2 / g≤S BET ≤120m 2 / g, for example, could be 20m 2 / g、40m 2 / g、60m 2 / g、80m 2 / g, 100m 2 / g or 120m 2 / g etc.

[0012] This application, by limiting the aforementioned structural parameters within a suitable range, helps ensure that the hollow silicon particles possess sufficient mechanical strength to maintain the integrity of the hollow structure, reserving ample buffer space for silicon volume expansion, while simultaneously limiting them in conjunction with tap density and specific surface area. Specifically: limiting δ to 20-80nm balances shell mechanical strength and lithium-ion diffusion path length, avoiding shell collapse due to excessively small δ or excessive absolute expansion due to excessively large δ; limiting φ to 30%-65% achieves a balance between cavity volume (buffer space) and silicon shell thickness (structural strength); and limiting ρ... tap Limited to 0.35-0.80 g / cm³ 3 S BET Limited to 20-120m 2 / g can synergistically regulate particle packing density and specific surface area, so that the batch consistency of materials and slurry processability can meet industrial requirements at the same time. In turn, it can work in synergy with the winding structure and heat dissipation characteristics of all-tab cylindrical batteries to suppress electrode expansion and thickness increase during cycling.

[0013] It should be noted that the shell wall thickness of the hollow silicon particles can be obtained by directly measuring the particle cross-section using a transmission electron microscope (TEM). Specifically, the hollow silicon particles are embedded, sliced, and their cross-sections are observed under a transmission electron microscope. The shell wall thickness of each particle is measured, and the arithmetic mean of at least 100 particles is taken as the shell wall thickness of the hollow silicon particles.

[0014] The hollowness ratio of hollow silicon particles is calculated by combining the particle density (ρparticle) of the hollow silicon particles with the true density of silicon: φ = (1 - ρparticle) / (ρparticle) particle / ρ Si ) × 100%, where ρ Si =2.33g / cm 3 The particle density ρ of hollow silicon particles particle The determination was performed using an organic liquid (such as kerosene or isopropanol) that does not react with silicon, via a specific gravity bottle method.

[0015] Furthermore, the porous silicon-carbon anode material has a porous structure, and its overall porosity can be determined by its tap density (ρ). tap Based on the silicon mass fraction measured by thermogravimetric analysis (TGA), the porosity is calculated as follows: Porosity = [1 - ρ tap / (w Si' ×ρ Si +(1-w Si' )×ρ C )]×100%, where w Si' ρ represents the mass fraction of silicon in the porous silicon-carbon anode material. Si =2.33g / cm3 , ρ C =2.2g / cm 3 .

[0016] The tap density of the porous silicon-carbon anode material was determined by a standard tap density meter (1000 taps, graduated cylinder method).

[0017] The specific surface area of ​​the porous silicon-carbon anode material was determined by nitrogen adsorption-desorption method (BET five-point method), which involves linear fitting of five points within the range of P / P0 = 0.05-0.3.

[0018] In some embodiments, δ and φ satisfy the following relationship: δ / φ≤1.5nm / %, for example, it can be 0.5nm / %, 0.8nm / %, 1.0nm / %, 1.2nm / % or 1.5nm / %, etc., and δ×(1-φ / 100)≥10nm, for example, it can be 10nm, 15nm, 20nm, 25nm or 30nm, etc.

[0019] This application specifies that δ and φ satisfy the above relationship, which can ensure that the hollow structure of the hollow silicon particles simultaneously meets the requirements of expansion buffer space and shell mechanical strength.

[0020] In some embodiments, the particle size D50 of the hollow silicon particles is 1-8 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm. It should be noted that the particle size D50 of the hollow silicon particles can be determined using a laser particle size analyzer.

[0021] In some embodiments, the ratio of the particle size D50 of the porous silicon-carbon anode material to the particle size D50 of the hollow silicon particles is 1-1.15, for example, it can be 1, 1.03, 1.06, 1.09, 1.12 or 1.15, etc.

[0022] This application limits the ratio of the particle size D50 of the porous silicon-carbon anode material to the particle size D50 of the hollow silicon particles to satisfy the above relationship. This is beneficial for forming a thin and dense carbon coating layer on the surface of the hollow silicon particles. This ensures the conductive network and structural constraint effect of the carbon coating layer on the hollow silicon-carbon particles, and avoids the increase of lithium-ion diffusion paths and the decrease of initial coulombic efficiency caused by excessive carbon coating layer.

[0023] In some embodiments, the carbon coating layer satisfies the following conditions: Based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 5-18 wt%, for example, it can be 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, or 18 wt%.

[0024] I D / IG =0.8-1.3, for example, it can be 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3, etc., where ID is the peak intensity of the D peak of the carbon coating layer and IG is the peak intensity of the G peak of the carbon coating layer.

[0025] This application specifies that the carbon coating layer meets the above conditions, which helps to form a dense carbon coating layer with a moderate degree of graphitization, thereby effectively isolating the electrolyte from direct contact with the silicon shell, inhibiting the continuous cracking and regeneration of the SEI film, and reducing irreversible capacity loss.

[0026] Oxidation temperature difference ΔT ox =T G -T C 50℃≤ΔTox≤80℃, where T C T represents the peak oxidation temperature of the carbon coating. G The peak temperature is the oxidation temperature of the graphite / carbon skeleton.

[0027] It should be noted that T G T C The mass content of the carbon coating can be determined by thermogravimetric analysis; I D / I G It can be determined by Raman spectroscopy.

[0028] In some embodiments, the porous silicon-carbon anode material has an initial delithiation specific capacity of ≥1200mAh / g at a 0.2C rate, such as 1200mAh / g, 1300mAh / g, 1400mAh / g, 1500mAh / g, or 1600mAh / g.

[0029] In some embodiments, the initial coulombic efficiency (ICE) of the porous silicon-carbon anode material during its first charge-discharge cycle at 0.2C satisfies: ICE ≥ 89% - 0.08 × δ.

[0030] In this application, the initial coulombic efficiency (ICE) of the porous silicon-carbon anode material is closely related to the shell wall thickness of the hollow silicon particles. By limiting the initial coulombic efficiency to the range of ICE ≥ 89% - 0.08 × δ, it is beneficial to ensure that while utilizing the shell wall thickness to provide expansion buffer and structural support, the initial coulombic efficiency deterioration caused by excessive wall thickness is avoided, thereby ensuring high initial efficiency while maintaining cycle stability.

[0031] In some embodiments, the first coulombic efficiency (ICE) of the porous silicon-carbon anode material during its first charge-discharge cycle at 0.2C satisfies: ICE ≥ 82.6%, for example, it can be 82.6%, 85%, 90%, 92%, 94%, or 96%, etc.

[0032] Secondly, this application provides a method for preparing a porous silicon-carbon anode material as described in the first aspect, the method comprising the following steps: Preparation of hollow silicon particles.

[0033] The hollow silicon particles are coated with carbon to obtain the porous silicon-carbon anode material.

[0034] In some embodiments, the preparation steps of the hollow silicon particles include: The template agent, magnesium powder, and chloride salt are mixed and subjected to magnesium thermal reduction treatment, followed by acid etching treatment to obtain the hollow silicon particles; wherein the template agent includes a silicon dioxide template agent; the preparation step also satisfies at least one of the following conditions: The particle size D50 of the silica template agent is 200-500nm, for example, it can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.

[0035] The molar ratio of the silica template agent to the magnesium powder is 1:(2-2.5), for example, it can be 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5, etc.

[0036] The mass ratio of the silica template agent to the chloride salt is 1:(7-9), for example, it can be 1:7, 1:7.5, 1:8, 1:8.5 or 1:9, etc.

[0037] The temperature of the magnesium thermal reduction treatment is 650-700℃, for example, 650℃, 660℃, 670℃, 680℃, 690℃ or 700℃, and the time is 4-6h, for example, 4h, 4.5h, 5h, 5.5h or 6h.

[0038] In some embodiments, the chloride salt includes potassium chloride and / or sodium chloride.

[0039] In this application, the shell wall thickness and hollowness of hollow silicon particles can be controlled by adjusting the particle size D50 of the silica template agent and the time of the magnesia reduction treatment.

[0040] In some embodiments, the carbon coating method includes chemical vapor deposition, and the process parameters include: a deposition temperature of 550-650℃, such as 550℃, 570℃, 590℃, 610℃, 630℃ or 650℃, and a deposition time of 0.5-2.5h, such as 0.5h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h or 2.5h.

[0041] Thirdly, this application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active substance, the negative electrode active substance comprising graphite material, and a porous silicon-carbon negative electrode material as described in the first aspect.

[0042] In some embodiments, the negative electrode sheet further includes a negative current collector.

[0043] In some embodiments, the negative current collector comprises copper foil.

[0044] In some embodiments, the thickness of the negative electrode current collector is 8-10 μm, for example, it can be 8 μm, 9 μm or 10 μm.

[0045] In some embodiments, the mass ratio of the porous silicon-carbon anode material to the graphite material is 1:(2-8), for example, it can be 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8, etc.

[0046] In this application, the appropriate mass ratio of porous silicon-carbon anode material to graphite material helps the porous silicon-carbon anode material provide sufficient reversible capacity to ensure high energy density. At the same time, the graphite material can effectively disperse silicon particles and buffer their volume expansion, avoiding structural damage or rapid capacity decay of the anode sheet due to excessive expansion.

[0047] In some embodiments, the compaction density of the negative electrode sheet is 1.4-1.7 g / cm³. 3 For example, it could be 1.4 g / cm³. 3 1.5g / cm 3 1.6g / cm 3 Or 1.7g / cm 3 wait.

[0048] In some embodiments, the areal density of the negative electrode sheet is 8-13 mg / cm³. 2 For example, it could be 8 mg / cm³ 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 Or 13mg / cm 2 wait.

[0049] In some embodiments, the negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max )≤0.1, for example, it can be 0.02, 0.04, 0.06, 0.08 or 0.1, etc., where ζ is the expansion suppression coefficient of the negative electrode, ΔT 600The thickness increment of the negative electrode sheet after 600 cycles at 1C (averaged thickness measured at 9 points using a micrometer), T0 is the thickness of the negative electrode sheet before cycling, and w Si γ is the mass fraction of porous silicon-carbon anode material relative to the total mass of the anode active material. max γ is the theoretical maximum volumetric expansion coefficient of Si. max =3.

[0050] The theoretical maximum volume expansion rate of Si is approximately 300%. In this application, γ is defined as... max is the theoretical maximum volume expansion coefficient of Si, with a value of 3.

[0051] It should be noted that ΔT 600 The method for determining / T0 is as follows: after 600 cycles at 1C, disassemble, rinse and dry with DMC, and take the average thickness at 9 points on a micrometer.

[0052] In some embodiments, the specific capacity of the negative electrode active material is ≥500 mAh / g, for example, it can be 510 mAh / g, 550 mAh / g, 600 mAh / g, 650 mAh / g, 700 mAh / g, or 750 mAh / g. It should be noted that "specific capacity of the negative electrode active material" refers to the reversible specific capacity of the negative electrode active material obtained by mixing porous silicon-carbon negative electrode material with graphite material.

[0053] In some embodiments, the capacity retention rate of the negative electrode active material after 600 cycles at 1C is ≥85%, for example, it can be 85%, 88%, 90%, 92%, 94% or 96%, etc.

[0054] In some embodiments, the initial coulombic efficiency of the negative electrode active material during its first charge-discharge cycle at 0.2C is ≥85%, for example, it can be 85%, 88%, 90%, 92%, 94%, or 96%.

[0055] In some embodiments, the negative electrode active material layer further includes a conductive agent and a binder. For example, the conductive agent may be conductive carbon black and / or carbon nanotubes, and the binder may be at least one of polyacrylic acid, sodium carboxymethyl cellulose, or styrene-butadiene rubber.

[0056] Fourthly, this application provides a fully tabbed cylindrical lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte.

[0057] Wherein, the negative electrode sheet is the negative electrode sheet described in the third aspect, or the negative electrode sheet includes the porous silicon-carbon negative electrode material as described in the first aspect.

[0058] It should be noted that the negative electrode tab is led out from the front end face of the negative electrode current collector and welded to the negative electrode cover plate.

[0059] In some embodiments, the all-tab cylindrical lithium-ion battery is a 4680 type or a 21650 type.

[0060] The 4680-type all-tab cylindrical lithium-ion battery meets at least one of the following conditions: The initial discharge capacity at 1C is ≥24Ah, for example, it can be 24Ah, 25Ah, 26Ah, 27Ah, or 28Ah, etc.; the areal density of the negative electrode sheet is 8-13 mg / cm³. 2 For example, it could be 8 mg / cm³ 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 Or 13mg / cm 2 The areal density of the positive electrode sheet is 35-50 mg / cm³. 2 For example, it could be 35 mg / cm³ 2 40mg / cm 2 45mg / cm 2 Or 50mg / cm 2 wait.

[0061] The 21650 type all-tab cylindrical lithium-ion battery meets at least one of the following conditions: The initial discharge capacity at 1C is ≥3Ah, for example, it can be 3Ah, 4Ah, 5Ah, 6Ah or 7Ah, etc.; the areal density of the negative electrode sheet is 8-13mg / cm³. 2 For example, it could be 8 mg / cm³ 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 Or 13mg / cm 2 The areal density of the positive electrode sheet is 28-42 mg / cm³. 2 For example, it could be 28 mg / cm³ 2 30mg / cm 2 35mg / cm 2 40mg / cm 2 Or 42mg / cm 2 wait.

[0062] It should be noted that for the 4680 type all-tab cylindrical battery, the core diameter is large and the number of electrode layers is high, requiring extremely high uniformity of electrode expansion—local differences in electrode expansion can lead to elliptical deformation of the core, seriously affecting battery safety and cycle life. For the 21650 type all-tab cylindrical battery, the core diameter is smaller and the number of electrode layers is fewer, resulting in less pressure on expansion uniformity, but higher requirements for electrode areal density and energy density.

[0063] In some embodiments, in the 4680 type, the N / P ratio is 1.06-1.12, for example, it can be 1.06, 1.08, 1.1 or 1.12, the core diameter is 38-42mm, for example, it can be 38mm, 40mm or 42mm, and the number of electrode layers is 60-80, for example, it can be 60 layers, 70 layers or 80 layers.

[0064] In some embodiments, the N / P ratio of the 21650 type is 1.06-1.12, for example, it can be 1.06, 1.08, 1.1 or 1.12, the core diameter is 16-19mm, for example, it can be 16mm, 17mm, 18mm or 19mm, and the number of electrode layers is 25-35, for example, it can be 25 layers, 30 layers or 35 layers.

[0065] In some embodiments, the all-tab cylindrical lithium-ion battery satisfies at least one of the following parameters: The capacity retention after 600 cycles at 1C / 1C rate is ≥85%, for example, it could be 85%, 88%, 90%, 92%, 94%, or 96%, etc.; the initial coulombic efficiency during the first charge-discharge cycle at 0.2C is ≥85%, for example, it could be 85%, 88%, 90%, 92%, 94%, or 96%, etc.; the electrode thickness expansion rate ΔT after 600 cycles is... 600 / T0≤20%, for example, it can be 5%, 10%, 12%, 15%, 18% or 20%, etc.

[0066] In some embodiments, the electrolyte contains film-forming additives.

[0067] Based on the total mass of the electrolyte, the film-forming additive includes 5-15% (e.g., 5%, 8%, 10%, 12% or 15%) of FEC (fluoroethylene carbonate) and 1-3% (e.g., 1%, 1.5%, 2%, 2.5% or 3%) of VC (ethylene carbonate).

[0068] This application, by adding the aforementioned mass fraction of film-forming additives to the electrolyte, facilitates the synergistic construction of a stable SEI film on the surfaces of porous silicon-carbon anode materials and graphite anodes. In conjunction with the porous silicon-carbon anode materials with specific shell wall thickness and porosity in this application, it can further reduce the expansion inhibition coefficient of the anode sheet and work synergistically with the heat dissipation structure of the all-tab cylindrical battery to reduce interfacial side reactions caused by local temperature rise.

[0069] The numerical range described in this application includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values ​​included in the range.

[0070] Compared with the prior art, this application has the following advantages: This application establishes a quantitative matching relationship between the shell wall thickness and the hollowness of hollow silicon particles, and synergistically limits the tap density and specific surface area of ​​porous silicon-carbon anode materials. This not only enables low-cost and rapid detection of batch consistency of products, but also allows the above structural parameters to be synergistically designed with the structure of all-tab cylindrical batteries, thereby effectively suppressing silicon volume expansion during cycling. This enables all-tab cylindrical batteries to achieve a synergistic improvement in high energy density and long cycle life. Detailed Implementation

[0071] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0072] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0073] In this application, "at least two combinations" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or at least two combinations" means any one of the listed items, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this application. In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this application, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.

[0074] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments that do not conflict with existing technologies. The ordinal numbers "first," "second," "third," and "fourth," etc., used in this application in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.

[0075] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.

[0076] Example 1 This embodiment provides a porous silicon-carbon anode material, which includes hollow silicon particles and a carbon coating layer covering the outer surface of the hollow silicon particles.

[0077] The porous silicon-carbon anode material satisfies the following conditions: δ=50nm, where δ is the shell wall thickness of the hollow silicon particle.

[0078] φ=48%, where φ is the hollowness of the hollow silicon particles.

[0079] ρ tap =0.55g / cm 3 , ρ tap The tap density is the porous silicon-carbon anode material.

[0080] S BET =58m 2 / g, S BET The specific surface area of ​​the porous silicon-carbon anode material is given.

[0081] The δ and φ satisfy the following relationship: δ / φ = 1.04nm / %, and δ × (1 - φ / 100) = 26nm.

[0082] The specific surface area of ​​the hollow silicon particles is 65m². 2 / g; the particle size D50 of the hollow silicon particles is 3.5μm; the ratio of the particle size D50 of the porous silicon-carbon anode material to the particle size D50 of the hollow silicon particles is 1.05.

[0083] The carbon coating layer satisfies the following condition: ΔT ox =T G -T C =68℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 12 wt%; I D / I G =1.05.

[0084] The porous silicon-carbon anode material has an initial delithiation specific capacity of 1780 mAh / g at a 0.2C rate; the initial coulombic efficiency (ICE) of the porous silicon-carbon anode material during the first charge-discharge cycle at 0.2C satisfies: ICE ≥ 89% - 0.08 × δ.

[0085] This embodiment also provides a method for preparing the above-mentioned porous silicon-carbon anode material, the method comprising the following steps: (1) Mix silica template agent with a particle size D50 of 300 nm and magnesium powder at a molar ratio of 1:2.2, and then mix with chloride salt (i.e., a mixed salt of sodium chloride and potassium chloride with a mass ratio of 1:1). Control the mass ratio of silica template agent and chloride salt to 1:8 to obtain a mixture.

[0086] (2) In an argon atmosphere, the temperature is raised to 680℃ and held for 5 hours for magnesium thermal reduction treatment.

[0087] The particles were cooled, then acid-washed with 1 mol / L hydrochloric acid to remove MgO and chloride salts, and then acid-etched with 5% hydrofluoric acid to remove unreacted silicon dioxide. After centrifugation, washing and drying, hollow silicon particles were obtained.

[0088] (3) The hollow silicon particles are placed in a CVD furnace and heated to 600°C. A mixture of argon and acetylene with a volume ratio of 90:10 is passed through the furnace at a total flow rate of 300 mL / min. The mixture is kept at this temperature for 1.5 h. After the process is completed, the mixture is cooled and passed through a 500-mesh sieve to obtain the porous silicon-carbon anode material.

[0089] This embodiment also provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer disposed on both sides of the negative electrode current collector; The negative electrode current collector is an 8μm thick electrolytic copper foil; the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder; the negative electrode active material includes graphite and the porous silicon-carbon negative electrode material as described above, with a mass ratio of the porous silicon-carbon negative electrode material to the graphite material of 1:3; the conductive agent includes conductive carbon black and carbon nanotubes; the binder includes polyacrylic acid, sodium carboxymethyl cellulose, and styrene-butadiene rubber; the mass ratio of the negative electrode active material, conductive carbon black, carbon nanotubes, polyacrylic acid, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 94:2:1:1:1:1.

[0090] The compaction density of the negative electrode sheet is 1.55 g / cm³. 3 The areal density of the negative electrode sheet on one side is 11.5 mg / cm³. 2 The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max )=0.065, ζ is the expansion suppression coefficient of the negative electrode, ΔT 600 T0 represents the thickness increment of the negative electrode sheet after 600 cycles at 1C, and T0 represents the thickness of the negative electrode sheet before cycling. Si The mass fraction of porous silicon-carbon anode material to the total mass of anode active material is wSi = 25%, γmax is the theoretical maximum volume expansion coefficient of Si (γmax = 3), and ΔT600 / T0 = 9.8%.

[0091] Specifically, ζ=(ΔT600 / T0) / (2×w) Si ×γ max)=0.098 / (2×0.25×3)=0.098 / 1.5=0.065, where, in the specific calculation of ζ, ΔT600 / T0 and w Si Take the decimal value; for example, in this embodiment, the value is ΔT600 / T0, which is 0.065. Si The value is 0.25. The calculation methods for other embodiments and comparative examples are the same as in Embodiment 1.

[0092] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, the method comprising the following steps: (i) The porous silicon-carbon anode material, graphite, conductive carbon black, carbon nanotubes, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber are dispersed in deionized water and planetarily stirred for 2 hours to obtain an anode slurry with a solid content of 45%.

[0093] (ii) The negative electrode slurry is coated on both sides of the electrolytic copper foil and then dried in hot air at 120°C until the moisture content is <500ppm.

[0094] The cells are cold-pressed to the target compaction density using two rollers, and then longitudinally and transversely cut. The longitudinal cut is made according to the battery model (580mm for the 4680 type and 610mm for the 21650 type), and the transverse cut is made according to the electrode length requirements.

[0095] The entire end face of the negative electrode copper foil is led out and ultrasonically welded to a 0.1mm nickel strip to form a negative electrode tab.

[0096] This embodiment also provides a 4680 type all-tab cylindrical lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte.

[0097] The negative electrode sheet is as described above; in the 4680 type, the areal density of the negative electrode sheet on one side is 11.5 mg / cm³. 2 The surface density of the positive electrode sheet is 42 mg / cm³. 2 The N / P ratio is 1.08, the core diameter is 40mm, and the number of electrode layers is 70. The electrolyte contains film-forming additives, which, based on the total mass of the electrolyte, include 10% FEC and 2% VC by mass. The design capacity of the 4680 type is 26Ah.

[0098] This embodiment also provides a method for preparing the above-mentioned all-tab cylindrical lithium-ion battery, the method comprising the following steps: (a) A negative electrode sheet is prepared according to the method for preparing the negative electrode sheet provided above.

[0099] (b) Preparation of the positive electrode sheet: Lithium nickel cobalt manganese oxide (NCM811) cathode material, polyvinylidene fluoride, conductive carbon black, carbon nanotubes and N-methylpyrrolidone were mixed and planetarily stirred for 3 hours to obtain a cathode slurry with a solid content of 72%; wherein the mass ratio of the NCM811 cathode material, polyvinylidene fluoride, conductive carbon black and carbon nanotubes was 94:3:2:1.

[0100] The positive electrode slurry was coated on both sides of an aluminum foil with a thickness of 12 μm, and then vacuum dried at 120 °C until the moisture content was <200 ppm.

[0101] Two-roll cold pressing to the target compaction density (3.3 g / cm³) 3 Then, longitudinal and transverse cuts are performed; the longitudinal cuts are made according to the battery model (the width of the 4680 model is 580mm), and the transverse cuts are made according to the electrode length requirements.

[0102] The entire end face of the positive electrode aluminum foil is led out and ultrasonically welded to a 0.1mm aluminum strip to form a positive electrode tab.

[0103] (c) Assemble a cylindrical battery with all tabs: Winding: The positive electrode sheet / PE ceramic coated diaphragm (16μm) / negative electrode sheet are wound on a fully automatic winding machine in the order of positive electrode sheet / PE ceramic coated diaphragm (16μm) / negative electrode sheet. The winding tension is controlled to be 4N for the positive electrode, 3N for the negative electrode and 2.5N for the diaphragm to obtain a 4680 type core.

[0104] Inserting into the shell: Insert the core into the aluminum shell; laser weld the negative electrode tab to the negative electrode cover plate, and laser weld the positive electrode tab to the bottom of the aluminum shell.

[0105] Injection: In a dry room with a dew point less than -40℃, inject 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte (EC:EMC=3:7, FEC mass fraction of 10wt%, VC mass fraction of 2wt%, injection coefficient of 3.2g / Ah) and let stand for 24h.

[0106] Sealing: Laser-welded cover plate to aluminum shell, helium leak detection rate <1×10 -5 Pa·m 3 / s.

[0107] Formation: 0.02C constant current charging to 3.0V → 0.05C constant current charging to 3.8V → 0.1C constant current and constant voltage charging to 4.2V (cutoff current 0.02C), with 30 minutes between each stage.

[0108] Capacity testing: Discharge at 0.5C constant current to 2.5V, charge at 0.5C constant current and constant voltage to 4.2V, repeat 3 times.

[0109] Aging: After being placed at 45℃ for 7 days, defective products with a self-discharge rate >5% were screened to obtain all-tab cylindrical batteries.

[0110] Example 2 The difference between this embodiment and Example 1 is that the particle size D50 of the silica template agent is 200 nm, δ=20 nm, φ=52%, and ρ... tap =0.48g / cm 3 S BET =95m 2 / g.

[0111] The remaining preparation methods and parameters are consistent with those in Example 1.

[0112] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.055.

[0113] Example 3 The difference between this embodiment and Example 1 is that the particle size D50 of the silica template agent is 260 nm, δ=35 nm, φ=50%, and ρ tap =0.52g / cm 3 S BET =78m 2 / g.

[0114] The remaining preparation methods and parameters are consistent with those in Example 1.

[0115] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.060.

[0116] Example 4 The difference between this embodiment and Example 1 is that the particle size D50 of the silica template agent is 400 nm, δ=65 nm, φ=45%, and ρ... tap =0.60g / cm 3 S BET =48m 2 / g.

[0117] The remaining preparation methods and parameters are consistent with those in Example 1.

[0118] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.075.

[0119] Example 5 The difference between this embodiment and Example 1 is that the particle size D50 of the silica template agent is 500 nm, the magnesium thermal reduction treatment time is 6 h, δ=80 nm, φ=40%, and ρ tap =0.65g / cm 3 S BET =35m 2 / g.

[0120] The remaining preparation methods and parameters are consistent with those in Example 1.

[0121] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.085.

[0122] Example 6 The difference between this embodiment and Embodiment 1 is that the particle size D50 of the silica template agent and the time of the magnesium thermal reduction treatment are adjusted so that φ=30% and ρ tap =0.72g / cm 3 S BET =28m 2 / g.

[0123] The remaining preparation methods and parameters are consistent with those in Example 1.

[0124] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.092.

[0125] Example 7 The difference between this embodiment and Embodiment 1 is that the particle size D50 of the silica template agent and the time of the magnesium thermal reduction treatment are adjusted so that φ=55% and ρ tap =0.50g / cm 3 S BET =72m 2 / g.

[0126] The remaining preparation methods and parameters are consistent with those in Example 1.

[0127] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.062.

[0128] Example 8 The difference between this embodiment and Embodiment 1 is that φ=65%, ρ tap =0.42g / cm 3 SBET =88m 2 / g.

[0129] The remaining preparation methods and parameters are consistent with those in Example 1.

[0130] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.058.

[0131] Example 9 The difference between this embodiment and embodiment 1 is that the heat preservation time in step (3) is 0.5 h, and the carbon coating layer meets the following conditions: ΔT ox =T G -T C =50℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 5 wt%; I D / I G =0.85; the specific surface area S of the porous silicon-carbon anode material BET =68m 2 / g.

[0132] The remaining preparation methods and parameters are consistent with those in Example 1.

[0133] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.072.

[0134] Example 10 The difference between this embodiment and embodiment 1 is that the heat preservation time in step (3) is 1 hour, and the carbon coating layer meets the following conditions: ΔT ox =T G -T C =60℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature is the value of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 9 wt%; I D / I G =0.95; the specific surface area S of the porous silicon-carbon anode material BET =62m 2 / g.

[0135] The remaining preparation methods and parameters are consistent with those in Example 1.

[0136] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.068.

[0137] Example 11 The difference between this embodiment and embodiment 1 is that the heat preservation time in step (3) is 2.5 hours, and the carbon coating layer meets the following conditions: ΔT ox =T G -T C =80℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature is the value of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 18 wt%; I D / I G =1.2; the specific surface area S of the porous silicon-carbon anode material BET =50m 2 / g.

[0138] The remaining preparation methods and parameters are consistent with those in Example 1.

[0139] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.060.

[0140] Example 12 The difference between this embodiment and Embodiment 1 is that the mass ratio of the porous silicon-carbon anode material to the graphite material is 1:2.

[0141] The remaining preparation methods and parameters are consistent with those in Example 1.

[0142] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.061.

[0143] Example 13 The difference between this embodiment and Embodiment 1 is that the mass ratio of the porous silicon-carbon anode material to the graphite material is 1:5.

[0144] The remaining preparation methods and parameters are consistent with those in Example 1.

[0145] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.082.

[0146] Example 14 The difference between this embodiment and Embodiment 1 is that the mass ratio of the porous silicon-carbon anode material to the graphite material is 1:8.

[0147] The remaining preparation methods and parameters are consistent with those in Example 1.

[0148] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.098.

[0149] Example 15 The difference between this embodiment and Embodiment 1 is that the areal density of the negative electrode sheet on one side is 8 mg / cm³. 2 .

[0150] The remaining preparation methods and parameters are consistent with those in Example 1.

[0151] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.058.

[0152] Example 16 The difference between this embodiment and Embodiment 1 is that the areal density of the negative electrode sheet on one side is 13 mg / cm³. 2 .

[0153] The remaining preparation methods and parameters are consistent with those in Example 1.

[0154] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.082.

[0155] Example 17 The difference between this embodiment and Embodiment 1 is that the type of the all-tab cylindrical lithium-ion battery is 21650, with a designed capacity of 5Ah; the single-sided areal density of the negative electrode sheet is 10mg / cm³. 2 The surface density of the positive electrode sheet is 35 mg / cm³. 2 The N / P ratio is 1.08, the core diameter is 17.5 mm, and the number of electrode layers is 30.

[0156] The remaining preparation methods and parameters are consistent with those in Example 1.

[0157] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max=0.062.

[0158] Example 18 The difference between this embodiment and Embodiment 1 is that the type of the all-tab cylindrical lithium-ion battery is 21650, with a designed capacity of 6Ah; the single-sided areal density of the negative electrode sheet is 12mg / cm³. 2 The surface density of the positive electrode sheet is 35 mg / cm³. 2 The N / P ratio is 1.08, the core diameter is 17.5 mm, and the number of electrode layers is 30.

[0159] The remaining preparation methods and parameters are consistent with those in Example 1.

[0160] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.068.

[0161] Example 19 The difference between this embodiment and Embodiment 1 is that the mass fraction of FEC in the electrolyte is 5%.

[0162] The remaining preparation methods and parameters are consistent with those in Example 1.

[0163] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.075.

[0164] Example 20 The difference between this embodiment and Embodiment 1 is that the mass fraction of FEC in the electrolyte is 8%.

[0165] The remaining preparation methods and parameters are consistent with those in Example 1.

[0166] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.070.

[0167] Example 21 The difference between this embodiment and Embodiment 1 is that the mass fraction of FEC in the electrolyte is 13%.

[0168] The remaining preparation methods and parameters are consistent with those in Example 1.

[0169] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.058.

[0170] Comparative Example 1 The difference between this comparative example and Example 1 is that the particle size D50 of the silica template agent was adjusted to 120 nm, resulting in δ=8 nm, φ=70%, and ρ tap =0.38g / cm 3 S BET =135m 2 / g.

[0171] The remaining preparation methods and parameters are consistent with those in Example 1.

[0172] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.052.

[0173] Comparative Example 2 The difference between this comparative example and Example 1 is that the particle size D50 of the silica template agent was adjusted to 600 nm, and the magnesium thermal reduction treatment time was 8 h, resulting in δ=120 nm, φ=25%, and ρ tap =0.78g / cm 3 .

[0174] The remaining preparation methods and parameters are consistent with those in Example 1.

[0175] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.16.

[0176] Comparative Example 3 The difference between this comparative example and Example 1 is that φ = 15%, ρ tap =0.85g / cm 3 S BET =18m 2 / g.

[0177] The remaining preparation methods and parameters are consistent with those in Example 1.

[0178] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.152.

[0179] Comparative Example 4 The difference between this comparative example and Example 1 is that φ=80%, ρ tap =0.30g / cm 3 S BET =145m2 / g.

[0180] The remaining preparation methods and parameters are consistent with those in Example 1.

[0181] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.048.

[0182] Comparative Example 5 The difference between this comparative example and Example 1 is that the heat preservation time in step (3) is 0.2 h, and the carbon coating layer meets the following conditions: ΔT ox =T G -T C =35℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 2 wt%; I D / I G =0.6; the specific surface area S of the porous silicon-carbon anode material BET =72m 2 / g.

[0183] The remaining preparation methods and parameters are consistent with those in Example 1.

[0184] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.085.

[0185] Comparative Example 6 The difference between this comparative example and Example 1 is that the heat preservation time in step (3) is 4 hours, and the carbon coating layer meets the following conditions: ΔT ox =T G -T C =95℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature of the graphite / carbon framework; based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 25 wt%; I D / I G =1.5; the specific surface area S of the porous silicon-carbon anode material BET =42m 2 / g.

[0186] The remaining preparation methods and parameters are consistent with those in Example 1.

[0187] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.058.

[0188] Comparative Example 7 The difference between this comparative example and Example 1 is that the mass ratio of the porous silicon-carbon anode material to the graphite material is 1:1.

[0189] The remaining preparation methods and parameters are consistent with those in Example 1.

[0190] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.107.

[0191] Comparative Example 8 The difference between this comparative example and Example 1 is that the areal density of the negative electrode sheet on one side is 5 mg / cm³. 2 .

[0192] The remaining preparation methods and parameters are consistent with those in Example 1.

[0193] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.048.

[0194] Comparative Example 9 The difference between this comparative example and Example 1 is that the areal density of the negative electrode sheet on one side is 16 mg / cm³. 2 .

[0195] The remaining preparation methods and parameters are consistent with those in Example 1.

[0196] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.122.

[0197] Comparative Example 10 The difference between this comparative example and Example 1 is that the mass fraction of FEC in the electrolyte is 2%.

[0198] The remaining preparation methods and parameters are consistent with those in Example 1.

[0199] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.092.

[0200] Comparative Example 11 The difference between this comparative example and Example 1 is that the mass fraction of FEC in the electrolyte is 18%.

[0201] The remaining preparation methods and parameters are consistent with those in Example 1.

[0202] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.063.

[0203] Comparative Example 12 The difference between this comparative example and Example 1 is that the all-tab cylindrical lithium-ion battery is replaced with a conventional single-tab cylindrical lithium-ion battery (the negative tab is a 3mm wide nickel strip single-point welded).

[0204] The remaining preparation methods and parameters are consistent with those in Example 1.

[0205] The negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max =0.082.

[0206] The key parameters in the above embodiments and comparative examples are summarized in Table 1. Table 1 Performance testing I. The porous silicon-carbon anode materials provided in the above embodiments and comparative examples were subjected to the first charge-discharge test in a coin cell with a lithium sheet as the counter electrode, within a voltage range of 0.01-1.5V, at a rate of 0.2C, to obtain the first delithiation specific capacity and the first coulombic efficiency (ICE).

[0207] II. The negative electrode sheets provided in the above embodiments and comparative examples were used to construct coin half-cells with lithium sheets as counter electrodes, and the following electrochemical tests were performed: (1) The first charge-discharge test was conducted under the conditions of voltage window 0.01-1.5V and rate 0.2C to obtain the first delithiation specific capacity and first coulombic efficiency ICE of the negative electrode active material.

[0208] (2) Perform constant current charge-discharge cycle test under voltage window of 0.01-1.5V and rate of 1C / 1C, record the discharge capacity after 600 cycles, and calculate the capacity retention rate.

[0209] III. Electrochemical performance tests were conducted on the all-tab cylindrical lithium-ion batteries provided in the above embodiments and comparative examples, including: Under the conditions of voltage window 0.01-1.5V and rate 1C / 1C, constant current charge-discharge cycle test was performed, the discharge capacity after 600 cycles was recorded, and the capacity retention rate was calculated. The first charge-discharge test was conducted under the conditions of voltage window 0.01-1.5V and rate 0.2C, and the first coulombic efficiency (ICE) was calculated.

[0210] A constant current charge-discharge cycle test was conducted under a voltage window of 0.01-1.5V and a rate of 1C / 1C. After 600 cycles, the battery was disassembled, the negative electrode was removed, and its thickness was measured according to the formula ΔT. 600 / T0×100% calculates the electrode thickness expansion rate.

[0211] The results are shown in Table 2.

[0212] Table 2 analyze: As shown in Table 2, δ is the core parameter determining the structural integrity and expansion buffering capacity of hollow silicon particles. When δ < 20 nm (Comparative Example 1, approximately 8 nm), the mechanical strength of the silicon shell is insufficient, and the shell is prone to collapse or breakage during electrode compaction and winding. The hollow structure loses its buffering function in the early stages of cycling. Although ζ = 0.052 seems low, this is an illusion caused by the dispersion of Si fragments after the shell breaks. In reality, the capacity retention rate of the fully tabbed cylindrical lithium-ion battery after 600 cycles is only 72.0%. When δ is in the range of 20-80 nm (Examples 2-5), the silicon shell has sufficient mechanical strength to maintain the integrity of the hollow structure. At the same time, the moderate wall thickness makes the lithium-ion diffusion path short and the polarization small. ζ increases monotonically from 0.055 (20 nm) to 0.085 (80 nm), and the capacity retention rate decreases from 85.0% to 83.0%. 50 nm is the optimal value overall. When δ>80nm (Comparative Example 2, approximately 120nm), the excessive wall thickness leads to excessive absolute expansion, and the cavity is insufficient to fully buffer it. ζ=0.16 exceeds the limit of 0.10, and the electrode expansion rate reaches 24.0%.

[0213] In addition, φ reflects the proportion of the cavity to the total volume of the particles, directly determining the size of the expansion buffer space. When φ is too low (<30%, Comparative Example 3, about 15%), the inner cavity volume is insufficient to accommodate the expansion of the silicon shell, and the buffering effect of the hollow structure is almost lost. ζ = 0.152, far exceeding 0.10, and the capacity retention rate of the all-tab cylindrical lithium-ion battery is only 78.0%. When φ is in the range of 30-65% (Examples 6-8), the cavity provides sufficient expansion buffer space, ζ decreases from 0.092 (30%) to 0.058 (65%), and the capacity retention rate of the all-tab cylindrical lithium-ion battery increases from 82.0% to 86.5%. When φ is too high (>65%, Comparative Example 4, about 80%), the silicon shell is too thin, and a large number of particles break during the mixing and coating process. tap Reduced to 0.30 g / cm³ 3 S BET Rise to 145m 2 / g, although ζ=0.048 seems excellent, the actual yield in the pulping process is extremely low, and it is not feasible for engineering.

[0214] In addition, the carbon coating is produced by the thermal decomposition of acetylene, ΔT ox This reflects the density and graphitization degree of the carbon coating. ΔT ox At temperatures below 50℃ (Comparative Example 5, approximately 35℃), the carbon coating layer is not dense enough to effectively isolate the electrolyte from the silicon shell, leading to continuous SEI growth. Consequently, the capacity retention of the all-tab cylindrical lithium-ion battery drops to 75.0%, with ζ = 0.085. ΔT ox Within the temperature range of 50–80°C (Examples 9–11), the carbon coating layer provides effective confinement without excessively hindering Li. + Diffusion, the capacity retention rate of all-tab cylindrical lithium-ion batteries remains at 84.5%~88.5%. ΔT ox Too high a temperature (Comparative Example 6, approximately 95°C) means that the carbon layer is too thick (25 wt%), resulting in a decrease in specific capacity.

[0215] Furthermore, the mass ratio of porous silicon-carbon anode material to graphite material determines the total amount of active Si in the anode, which is a key variable in balancing energy density and cycle stability. At a mass ratio of 1:2 (Example 12), the specific capacity of the anode active material in the anode sheet reaches 820 mAh / g, and the capacity retention of the all-tab cylindrical lithium-ion battery is 84.0%. A mass ratio of 1:3 (Example 1 baseline) is generally better. At a mass ratio of 1:8 (Example 14), the capacity retention of the all-tab cylindrical lithium-ion battery is 90.0%, but the specific capacity of the anode active material in the anode sheet is only 520 mAh / g. Beyond 1:2 (Comparative Example 7, 1:1), ζ = 0.107, exceeding 0.10, and the capacity retention of the all-tab cylindrical lithium-ion battery drops to 76.5%.

[0216] In addition, the areal density of the negative electrode is too low (<8mg / cm³). 2 Comparative example 8.5 mg / cm 2 When the battery energy density is insufficient, the areal density on one side is too high (>13mg / cm³). 2 Comparative Example 9, 16 mg / cm 2 When the electrode sheet is too thick, the interlayer stress increases after winding, and the cumulative effect of Si expansion is significant. ζ=0.122 exceeds 0.10, and the capacity retention rate of the full-tab cylindrical lithium-ion battery drops to 72.0%.

[0217] In addition, the 4680 type battery has a large core diameter and many electrode layers, requiring extremely high uniformity of electrode expansion. Example 1 (4680 type) has a ζ=0.065 and a capacity retention rate of 88.5%. The 21650 type battery has a small core diameter and fewer electrode layers, resulting in lower pressure for expansion uniformity. Example 17 (21650 type) has a ζ=0.062 and a capacity retention rate of 89.5%; Example 18 (21650 type, 12mg / cm³) 2 The capacitance value of the full-tab structure is ζ=0.068, and the capacity retention rate is 87.0%. The capacitance value of the comparative example 12 (4680 type monopole) is ζ=0.082, and the capacity retention rate is 80.5%. The above data show that the full-tab structure improves the capacity retention rate by about 8 percentage points by reducing the local temperature rise at the tab.

[0218] Furthermore, since FEC decomposition products (LiF and organofluorine compounds) form a fluorine-rich interface layer on the Si surface, insufficient FEC (comparative Example 10, 2 wt%) results in inadequate interface protection, with ζ=0.092, and the capacity retention of the all-tab cylindrical lithium-ion battery is only 78.0%. Excessive FEC (comparative Example 11, 18 wt%) leads to severe decomposition and gas generation, reducing the capacity retention of the all-tab cylindrical lithium-ion battery to 82.0%. Therefore, an FEC mass fraction of 5-15 wt% exhibits the best synergistic effect with the carbon coating layer.

[0219] It should be noted that this application illustrates the process method through the above embodiments, but this application is not limited to the above process steps, that is, it does not mean that this application must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the raw materials used in this application, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.

Claims

1. A porous silicon-carbon anode material, characterized in that, The porous silicon-carbon anode material includes hollow silicon particles and a carbon coating layer covering the outer surface of the hollow silicon particles. The porous silicon-carbon anode material satisfies the following conditions: 20nm≤δ≤80nm, where δ is the shell wall thickness of the hollow silicon particle; 30%≤φ≤65%, where φ is the hollowness of the hollow silicon particles; 0.35g / cm 3 ≤ρ tap ≤0.80g / cm 3 , ρ tap The tap density of the porous silicon-carbon anode material; 20m 2 / g≤S BET ≤120m 2 / g, S BET The specific surface area of ​​the porous silicon-carbon anode material is given.

2. The porous silicon-carbon anode material according to claim 1, characterized in that, The δ and φ satisfy the following relationship: δ / φ≤1.5nm / %, and δ×(1-φ / 100)≥10nm; And / or, the particle size D50 of the hollow silicon particles is 1-8 μm; And / or, the ratio of the particle size D50 of the porous silicon-carbon anode material to the particle size D50 of the hollow silicon particles is 1-1.

15.

3. The porous silicon-carbon anode material according to claim 1 or 2, characterized in that, The carbon coating layer must satisfy at least one of the following conditions: Based on the total mass of the porous silicon-carbon anode material, the mass content of the carbon coating layer is 5-18 wt%. I D / I G =0.8-1.3, where I D The peak intensity of the D peak of the carbon coating layer, I G The peak intensity of the G peak is the carbon coating layer; Oxidation temperature difference ΔT ox =T G -T C 50℃≤ΔTox≤80℃, where T C T represents the oxidation peak temperature of the carbon coating. G The oxidation peak temperature is for the graphite / carbon skeleton.

4. The porous silicon-carbon anode material according to claim 1 or 2, characterized in that, The porous silicon-carbon anode material has an initial delithiation specific capacity of ≥1200mAh / g at a 0.2C rate; And / or, the initial coulombic efficiency (ICE) of the porous silicon-carbon anode material during its first charge-discharge cycle at 0.2C satisfies: ICE ≥ 89% - 0.08 × δ.

5. A method for preparing a porous silicon-carbon anode material as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: Preparation of hollow silicon particles; The hollow silicon particles are coated with carbon to obtain the porous silicon-carbon anode material.

6. The preparation method according to claim 5, characterized in that, The preparation steps of the hollow silicon particles include: The template agent, magnesium powder, and chloride salt are mixed and subjected to magnesium thermal reduction treatment, followed by acid etching treatment to obtain the hollow silicon particles; wherein the template agent includes a silicon dioxide template agent; the preparation step also satisfies at least one of the following conditions: The particle size D50 of the silica template agent is 200-500 nm; The molar ratio of the silica template agent to the magnesium powder is 1:(2-2.5); The mass ratio of the silica template agent to the chloride salt is 1:(7-9); The magnesium thermal reduction treatment is performed at a temperature of 650-700℃ for 4-6 hours. And / or, the carbon coating method includes chemical vapor deposition, with process parameters including: deposition temperature of 550-650℃ and deposition time of 0.5-2.5h.

7. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active substance, the negative electrode active substance includes graphite material, and the porous silicon-carbon negative electrode material as described in any one of claims 1-4.

8. The negative electrode sheet according to claim 7, characterized in that, The mass ratio of the porous silicon-carbon anode material to the graphite material is 1:(2-8); And / or, the compaction density of the negative electrode sheet is 1.4-1.7 g / cm³. 3 ; And / or, the areal density of the negative electrode sheet on one side is 8-13 mg / cm³. 2 ; And / or, the negative electrode plate satisfies: ζ=(ΔT) 600 / T0) / (2×w Si ×γ max )≤0.1, ζ is the expansion suppression coefficient of the negative electrode, ΔT 600 T0 represents the thickness increment of the negative electrode after 600 cycles at 1C, and T0 represents the initial thickness of the negative electrode. Si γ represents the mass fraction of porous silicon-carbon anode material relative to the total mass of the anode active material. max γ is the theoretical maximum volume expansion factor of Si. max =3; And / or, the specific capacity of the negative electrode active material is ≥500mAh / g; And / or, the capacity retention rate of the negative electrode active material after 600 cycles at 1C is ≥85%; And / or, the initial coulombic efficiency of the negative electrode active material during its first charge-discharge cycle at 0.2C is ≥85%.

9. A cylindrical lithium-ion battery with multiple tabs, characterized in that, The all-tab cylindrical lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. Wherein, the negative electrode sheet is the negative electrode sheet according to claim 7 or 8, or the negative electrode sheet comprises the porous silicon-carbon negative electrode material according to any one of claims 1-4.

10. The all-tab cylindrical lithium-ion battery according to claim 9, characterized in that, The all-tab cylindrical lithium-ion battery is either a 4680 type or a 21650 type. The 4680-type all-tab cylindrical lithium-ion battery meets at least one of the following conditions: 1C initial discharge capacity ≥24Ah; single-sided areal density of the negative electrode is 8-13mg / cm³. 2 The areal density of the positive electrode sheet is 35-50 mg / cm³. 2 ; The 21650 type all-tab cylindrical lithium-ion battery meets at least one of the following conditions: 1C initial discharge capacity ≥3Ah; single-sided areal density of the negative electrode is 8-13mg / cm³. 2 The areal density of the positive electrode sheet is 28-42 mg / cm³. 2 .

11. The all-tab cylindrical lithium-ion battery according to claim 9 or 10, characterized in that, The full-tab cylindrical lithium-ion battery satisfies at least one of the following parameters: Capacity retention ≥85% after 600 cycles at 1C / 1C rate; initial coulombic efficiency ≥85% during the first charge-discharge cycle at 0.2C; electrode thickness expansion ΔT after 600 cycles. 600 / T0≤20%; And / or, the electrolyte contains film-forming additives; Based on the total mass of the electrolyte, the film-forming additives include 5-15% FEC and 1-3% VC by mass.